At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the problem, we'll use the fact that in a triangle, the centroid (M) divides each median into a ratio of 2:1, meaning [tex]\( BM = 2 \cdot MQ \)[/tex].
Given the lengths:
[tex]\[ BM = 9x \][/tex]
[tex]\[ MQ = 5x - 1 \][/tex]
We set up the equation from the provided information:
[tex]\[ BM = 2 \cdot MQ \][/tex]
Substitute the given expressions for [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ 9x = 2 \cdot (5x - 1) \][/tex]
Now, let's solve this equation step-by-step.
1. Distribute the 2 on the right side:
[tex]\[ 9x = 2 \cdot 5x - 2 \cdot 1 \][/tex]
[tex]\[ 9x = 10x - 2 \][/tex]
2. Bring the [tex]\( 10x \)[/tex] term to the left side by subtracting [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 9x - 10x = -2 \][/tex]
[tex]\[ -x = -2 \][/tex]
3. Multiply both sides by -1 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 2 \][/tex]
Now that we have [tex]\( x \)[/tex], let's find the length of [tex]\( BQ \)[/tex]. The segment [tex]\( BQ \)[/tex] is the sum of [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ BQ = BM + MQ \][/tex]
Substitute the expressions for [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ BQ = 9x + (5x - 1) \][/tex]
Now, substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ BQ = 9(2) + 5(2) - 1 \][/tex]
[tex]\[ BQ = 18 + 10 - 1 \][/tex]
[tex]\[ BQ = 27 \][/tex]
Therefore, the correct values are [tex]\( x = 2 \)[/tex] and [tex]\( BQ = 27 \)[/tex].
The correct answer is:
A. [tex]\( x = 2 \)[/tex] and [tex]\( BQ = 27 \)[/tex]
Given the lengths:
[tex]\[ BM = 9x \][/tex]
[tex]\[ MQ = 5x - 1 \][/tex]
We set up the equation from the provided information:
[tex]\[ BM = 2 \cdot MQ \][/tex]
Substitute the given expressions for [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ 9x = 2 \cdot (5x - 1) \][/tex]
Now, let's solve this equation step-by-step.
1. Distribute the 2 on the right side:
[tex]\[ 9x = 2 \cdot 5x - 2 \cdot 1 \][/tex]
[tex]\[ 9x = 10x - 2 \][/tex]
2. Bring the [tex]\( 10x \)[/tex] term to the left side by subtracting [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 9x - 10x = -2 \][/tex]
[tex]\[ -x = -2 \][/tex]
3. Multiply both sides by -1 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 2 \][/tex]
Now that we have [tex]\( x \)[/tex], let's find the length of [tex]\( BQ \)[/tex]. The segment [tex]\( BQ \)[/tex] is the sum of [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ BQ = BM + MQ \][/tex]
Substitute the expressions for [tex]\( BM \)[/tex] and [tex]\( MQ \)[/tex]:
[tex]\[ BQ = 9x + (5x - 1) \][/tex]
Now, substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ BQ = 9(2) + 5(2) - 1 \][/tex]
[tex]\[ BQ = 18 + 10 - 1 \][/tex]
[tex]\[ BQ = 27 \][/tex]
Therefore, the correct values are [tex]\( x = 2 \)[/tex] and [tex]\( BQ = 27 \)[/tex].
The correct answer is:
A. [tex]\( x = 2 \)[/tex] and [tex]\( BQ = 27 \)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.